Bridging the Gap Between Mesoscopic Transport Planning and Microscopic Traffic Simulation: An Analytical and Numerical Analysis of Traffic Dynamics. Issue 5 (May 2023) - Triebke, Henriette; Kromer, Markus; Vortisch, Peter
Usage profiles of shared autonomous fleets will considerably differ from present-day privately owned vehicles. Thus, requirements on powertrain and other vehicle components are expected to change significantly. While there are still no real-world data available, automotive requirement engineering strongly depends on synthetic driving profiles, for example, forwarded by traffic simulation. These simulations, however, are quite challenging as they need to combine multi-modal, large-scale fleet simulations with microscopic traffic modeling to simultaneously produce realistic usage profiles and detailed driving cycles. We aim to combine the two open-source tools MATSim and SUMO to achieve this goal. As an important step in this endeavor, we analyze the consistency of both MATSim and SUMO with regard to traffic dynamics by means of three experiments with an increasing level of complexity: (i) analytically on a homogeneous road segment in the steady-state; (ii) numerically on a homogeneous road segment in the non-stationary state for a synthetic test case; and (iii) numerically for a highly non-linear medium-sized real-world test case in Berlin. We analyze the simulation results with respect to macroscopic flow–density–speed relations. In addition, we also study network impedances for the Berlin test case. We show that the traffic dynamics of MATSim and SUMO behave differently for the various test cases and discuss the implications on our tool-coupling efforts.